The Impact of Environmental Performance, Green Accounting, And Corporate Social Responsibility (CSR) on Financial Performance - Tjandrakirana DP, Rina; Ermadiani, Ermadiani; Aspahani Aspahani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study aims to test and find empirical evidence on the impact of environmental performance, green accounting, and Corporate Social Responsibility (CSR) on financial performance. The type of data used is secondary data in the form of annual reports of health service companies listed on the Indonesia Stock Exchange in 2018-2023. The dependent variable in this study is financial performance, while the independent variables consist of environmental performance, green accounting, and Corporate Social Responsibility (CSR). The analysis technique used is the classical assumption test consisting of the normality test, multicollinearity test, autocorrelation test heteroscedasticity test, and hypothesis testing including multiple linear regression, individual parameter significance test (t-test), simultaneous significance test (F test) and coefficient of determination. The sampling technique was carried out using a purposive sampling method, obtaining as many as 30 health service companies registered on the IDX in 2018-2023. The results of this study indicate that environmental performance affects financial performance, green accounting affects financial performance, while Corporate Social Responsibility (CSR) does not affect financial performance.